Nickel@Nickel Oxide Dendritic Architectures with Boosted Electrochemical Reactivity for Aqueous Nickel–Zinc Batteries. Issue 22 (14th October 2020) - Wang, Fuxin; Lu, Yongzhuang; Zeng, Siqi; Song, Yin; Zheng, Dezhou; Xu, Wei; Lu, Xihong
Abstract: Rechargeable alkaline zinc‐ion batteries (ZIBs) have gained extensive attention on account of their inexpensiveness, and high levels of safety and output voltage, but the lack of suitable cathode materials with high energy storage property and long cycle stability limits further development of ZIBs. Herein, we report an effective two‐step electrochemical approach to prepare Ni@NiO core‐shell dendritic architectures as cathode material for rechargeable alkaline ZIBs. Benefiting from the highly active NiO shell and unique core‐shell structure, this Ni@NiO electrode shows an excellent discharge capacity (0.112 mAh cm −2, at 4 mA cm −2 ) and a high rate capability (63.7 % capacity retention at 40 mA cm −2 ). Furthermore, the alkaline ZIBs with this Ni@NiO cathode also displays a high energy density of 0.193 mWh cm −2 and a remarkable power density of 65.0 mW cm −2 . Abstract : If I had a nickel : A convenient and efficient method is developed to synthesize the binder‐free highly active core‐shell Ni@NiO electrode. Benefiting from the in situ formation of highly active NiO shell, the Ni@NiO electrode displays better electrochemical activity. The alkaline zinc‐ion batteries with this electrode exhibits a greater discharge capacity (0.112 mAh cm −2, at 4 mA cm −2 ), and outstanding cycle stability (only ∼7 % capacity losses after 20000 cycles)